2023
DOI: 10.1002/pc.27215
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mechanical, ballistic and tribological behavior of luffa aegyptiaca fiber reinforced coco husk biochar epoxy composite

Abstract: In the current work, light weight epoxy bio‐composites are created for low‐cost technological applications using luffa aegyptiaca fiber and biochar particles derived from coco husk (CHB). This study aims to evaluate the effects of CHB particles added at different concentrations (3 vol% and 5 vol%) on the dynamic mechanical, ballistic and tribology behavior of epoxy composites constructed from luffa aegyptiaca fiber with different fiber loading (20%, 30% and 40 vol%). The composites are prepared using hand layu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…As the temperature increased, the wear rates of the samples all showed an increasing trend, and this trend was particularly pronounced in the 300–350 range. When the friction surface temperature increased, the resin binder gradually relaxed and thermally decomposed, and the filler particles embedded in it flaked off and filled the friction surface to form a three‐body wear, which further increased the wear rate 26 . Moreover, the wear rates of the RSF‐added specimens were lower than those of the unadded ones at all test temperatures, suggesting that the addition of RSF is beneficial to the improvement of wear resistance because it contributes to the formation of the tribo‐film.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the temperature increased, the wear rates of the samples all showed an increasing trend, and this trend was particularly pronounced in the 300–350 range. When the friction surface temperature increased, the resin binder gradually relaxed and thermally decomposed, and the filler particles embedded in it flaked off and filled the friction surface to form a three‐body wear, which further increased the wear rate 26 . Moreover, the wear rates of the RSF‐added specimens were lower than those of the unadded ones at all test temperatures, suggesting that the addition of RSF is beneficial to the improvement of wear resistance because it contributes to the formation of the tribo‐film.…”
Section: Resultsmentioning
confidence: 99%
“…When the friction surface temperature increased, the resin binder gradually relaxed and thermally decomposed, and the filler particles embedded in it flaked off and filled the friction surface to form a threebody wear, which further increased the wear rate. 26 Moreover, the wear rates of the RSF-added specimens were lower than those of the unadded ones at all test temperatures, suggesting that the addition of RSF is beneficial to the improvement of wear resistance because it contributes to the formation of the tribo-film. Figure 7B shows the comparison of the sum wear rate of the five samples, with the increase of RSF addition, the sum wear rate first decreases and then increases.…”
Section: Wear Resistance Analysismentioning
confidence: 87%
“…However, only the complex axial modulus of fibers can be measured by dynamic mechanical analysis (DMA), and the radial complex modulus of fibers cannot be measured directly. [5][6][7][8] It has been confirmed that the damping of fibers cannot be ignored in composite design calculations. [2,3] There are three kinds of fiber damping assumptions: linear elasticity, [9][10][11][12][13][14][15] isotropic damping [5,[16][17][18][19][20][21][22][23] and anisotropic damping.…”
Section: Introductionmentioning
confidence: 98%
“…However, only the complex axial modulus of fibers can be measured by dynamic mechanical analysis (DMA), and the radial complex modulus of fibers cannot be measured directly. [ 5–8 ]…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37][38] Research efforts are therefore underway to develop different designs to improve the energy absorption capacity of para-aramid fabrics through interply/intraply hybridization with different types of synthetic and natural fibers, layering of different materials or matrices and impregnation with STF, micro/nano-particles or the combination of these. [39][40][41] However, the contribution of polymer-based nanofiber mats to the ballistic impact response of the textile laminated armor system has not yet been reported in the open literature, despite the promising improvement in the mechanical properties of composites with a very small nanofiber reinforcement (<10 wt%) due to their extremely high surface area/mass ratio.…”
Section: Introductionmentioning
confidence: 99%